Pengaruh Model Pembelajaran Problem Posing Berbantuan Platform Wordwall terhadap Hasil Belajar Siswa di SMKN 1 Lamongan - Nurul Aprilia Indah Wardani; Durinta Puspasari (EduInovasi: Journal of Basic Educational Studies, 2025)
The low academic achievement of students in the 10th grade Office Management class at SMKN 1 Lamongan shows how important innovation is in teaching. This study offers new ideas by combining the Problem Posing approach and the interactive digital tool Wordwall, which has not been widely researched. The point of this inquire about is to assess the affect of the Issue. On understudy learning comes about at SMKN 1 Lamongan, the Wordwall Stage is utilized to display a learning show. A quasi-experimental plan with two bunches was utilized in this think about: an test gather that utilized the Issue Posturing learning demonstrate in conjunction with the a control gather utilizing the Coordinate Instruction learning demonstrate and the Wordwall Platform's bolster. The information was subjected to pre- and post-tests utilizing parametric factual examination. Compared to the control gather, the exploratory course appeared a impressive enhancement in understudy learning results, concurring to the comes about of this think about (p < 0. 05). It is prescribed that the Issue Posturing learning demonstrate helped by the Wordwall Stage be broadly executed in schools with the back of adequate innovative facilities to extend adequacy within the learning prepare.